Horizontal gene transfer from diverse bacteria to an insect genome enables a tripartite nested mealybug symbiosis - Husnik, Filip; Nikoh, Naruo; Koga, Ryuichi; Ross, Laura; Duncan, Rebecca P; Fujie, Manabu; Tanaka, Makiko; Satoh, Nori; Bachtrog, Doris; Wilson, Alex C C; von Dohlen, Carol D; Fukatsu, Takema; et al. (Cell, 2013)
The smallest reported bacterial genome belongs to Tremblaya princeps, a symbiont of Planococcus citri mealybugs (PCIT). Tremblaya PCIT not only has a 139 kb genome, but possesses its own bacterial endosymbiont, Moranella endobia. Genome and transcriptome sequencing, including genome sequencing from a Tremblaya lineage lacking intracellular bacteria, reveals that the extreme genomic degeneracy of Tremblaya PCIT likely resulted from acquiring Moranella as an endosymbiont. In addition, at least 22 expressed horizontally transferred genes from multiple diverse bacteria to the mealybug genome likely complement missing symbiont genes. However, none of these horizontally transferred genes are from Tremblaya, showing that genome reduction in this symbiont has not been enabled by gene transfer to the host nucleus. Our results thus indicate that the functioning of this three-way symbiosis is dependent on genes from at least six lineages of organisms and reveal a path to intimate endosymbiosis distinct from that followed by organelles.
Keywords: Gene Transfer, Horizontal; Animals; Phylogeny; přenos genů horizontální; Amino Acids; Betaproteobacteria; symbióza; zvířata; molekulární sekvence - údaje; Hemiptera; Molecular Sequence Data; fylogeneze; aminokyseliny; Symbiosis; Bacteria; Gene Expression Profiling; stanovení celkové genové exprese